Penerapan Fungsi Manajemen Pendidikan Dalam Meningkatkan Mutu Pembelajaran ISMUBA di SMP Muhammadiyah 1 Makassar - Abdul Rahman, Husain; Saleh, Syamsudduha; Siraj , Arifuddin; Mawardi, Amirah (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2023)
This study aims to determine the application of Management functions to ISMUBA learning at SMP Muhammadiyah 1 Makassar and ISMUBA joint learning at SMP Muhammadiyah 1 Makassar. The results of this study indicate that: First, the implementation of the education management function is very good, this is evidenced by the fulfillment of the stages: lesson planning, organizing, coordinating, implementing, monitoring and evaluating. Second, the quality of ISMUBA learning at SMP Muhammadiyah 1 Makassar is good because of the emphasis on: increasing worship and morals, growing social life, increasing self-confidence, increasing critical reasoning by participating in extracurricular activities and growing a creative spirit. Third, the implementation of education management functions namely planning, implementation and evaluation and Fourth, factors that support the implementation of management functions related to the performance of school principals, professional teachers, learning media and infrastructure. The inhibiting factor is the awareness of parents and students about the importance of quality education to provide support and limited funds for the benefit of learning quality improvement programs.